A systematic review and meta‐analysis on oncological radiotherapy in patients with a cardiac implantable electronic device: Prevalence and predictors of device malfunction in 3121 patients. (7th September 2022) - Malavasi, Vincenzo Livio; Imberti, Jacopo Francesco; Tosetti, Alberto; Romiti, Giulio Francesco; Vitolo, Marco; Zecchin, Massimo; Mazzeo, Ercole; Giuseppina, De Marco; Lohr, Frank; Lopez‐Fernandez, Teresa; Boriani, Giuseppe
Abstract: Background: The number of patients with cardiac implantable electronic devices (CIEDs) undergoing radiotherapy (RT) for cancer treatment is growing. At present, prevalence and predictors of RT‐induced CIEDs malfunctions are not defined. Methods: Systematic review and meta‐analysis conducted following the PRISMA recommendations. PubMed, Scopus and Google Scholar were searched from inception to 31/01/2022 for studies reporting RT‐induced malfunctions in CIEDs patients. Aim was to assess the prevalence of RT‐induced CIEDs malfunctions and identify potential predictors. Results: Thirty‐two out of 3962 records matched the inclusion criteria and were included in the meta‐analysis. A total of 135 CIEDs malfunctions were detected among 3121 patients (6.6%, 95% confidence interval [CI]: 5.1%–8.4%). The pooled prevalence increased moving from pacemaker (PM) to implantable cardioverter defibrillator (ICD), and cardiac resynchronization therapy and defibrillator (CRT‐D) groups (4.1%, 95% CI: 2.9–5.8; 8.2% 95% CI: 5.9–11.3; and 19.8%, 95% CI: 11.4–32.2 respectively). A higher risk ratio (RR) of malfunctions was found when neutron‐producing energies were used as compared to non‐neutron‐producing energies (RR 9.98, 95% CI: 5.09–19.60) and in patients with ICD/CRT‐D as compared to patients with PM/CRT‐P (RR 2.07, 95% CI: 1.40–3.06). On the contrary, no association was found between maximal radiation dose at CIED >2 Gy and CIEDs malfunctions (RR 0.93; 95% CI: 0.31–2.76). Conclusions: Radiotherapy related CIEDs malfunction had a prevalence ranging from 4% to 20%. The use of neutron‐producing energies and more complex devices (ICD/CRT‐D) were associated with higher risk of device malfunction, while the radiation dose at CIED did not significantly impact on the risk unless higher doses (>10 Gy) were used.